PERMINTAAN PEMBIAYAAN UMKM KE PERBANKAN SYARIAH DI SUMATERA BARAT - Neng Kamarni; Hefrizal Handra (Maqdis: Jurnal Kajian Ekonomi Islam, 2019)
The demand forIslamic financing from Micro, Small and Medium Enterprises (MSMEs) is important to be analyzed since they have a significant role in employment and the source of living for community. Quantitatively, the income and profits of MSMEs have a big impact on the gross regional domestic product (GRDP) where the MSMEs are located. They can be one of the drivers of the real sector of economy to improve the welfare of the community. The Islamic financing scheme is an alternative to strengthen the MSMEs and this is in line with the culture of the people of West Sumatra. This study aims to analyze the factors related to the demand for Islamic banking financing in helping micro, small and medium businesses to finance the capital expenditure in West Sumatra. The data used in this research is directly collected from the field. About 100 samples are chosen from 3,105 MSMEs that have already accessed capital financing from various Islamic Bank in West Sumatra. A crosstab analysis is used and tested using the Chi-Square method based on probability. One important finding of this study is that the bigger the size of capital financing, the bigger the probability of MSMEs to increase the income.